"We Have to Educate Every Single Student, Not Just the Ones That Look Like Us": Support Service Providers' Beliefs About the Root Causes of the School-to-Prison Pipeline for Youth of Color. Issue 3 (2nd October 2018) - Yang, Jessica L.; Anyon, Yolanda; Pauline, Malina; Wiley, Katherine E.; Cash, Donna; Downing, Barbara J.; Greer, Eldridge; Kelty, Ellen; Morgan, Thomas Lee; Pisciotta, Lisa
Abstract: This study adds to the extant research on the school-to-prison pipeline by investigating how school-based service providers and administrators conceptualize the causal mechanisms constraining and enabling the school-to-prison pipeline in a large urban district. Thirty-three schools were selected for the study based on their suspension rates. Support staff and district partners ( n  = 36) participated in focus groups guided by semi-structured protocols. Most participants emphasized structural and systemic causes of the school-to-prison pipeline, such as institutional racism and poverty. To minimize the school-to-prison pipeline, participants highlighted the importance of relationship building and non-punitive practices in response to misbehavior, although solutions offered limited evidence of promising interventions. Given strong research indicating that racial disparities cannot be explained by differential behavior, scholarship in this area emphasizes the need to increase school-level practices that promote positive school climate. The persistence of exclusionary and punitive attitudes among a subset of the sample suggests a need for differentiated professional development to address competing frameworks for understanding the root causes of, and solutions to, the school-to-prison pipeline.